2016
DOI: 10.18203/issn.2455-4510.intjresorthop20164173
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of femoral neck shaft angle on plain radiographs and its clinical implications

Abstract: <p class="abstract"><strong>Background:</strong> The femoral neck-shaft angle is the measurement of the angle formed between the oblique oriented neck with the vertical shaft and is an important anatomic measurement for the evaluation of biomechanics of hip.<span> The neck shaft angle is important in surgeries that involve the neck of femur, Intertrochanteric fractures, slipped capital femoral epiphysis, and developmental dysplasia of hip. Different variation of neck shaft angle has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
3
2
0
Order By: Relevance
“…In another study done by Rogers et al [28] on 203 patients to check for side-to-side variability of the FNSA using upright anteroposterior pelvis radiographs, no significant variability between the two angles was found. Similarly, a study done in India on 110 patients using supine anteroposterior pelvis radiographs concluded that the NSA angle of the contralateral femur can be used as a template during repair [29]. Both studies [28,29] mentioned above agrees with findings of this present study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In another study done by Rogers et al [28] on 203 patients to check for side-to-side variability of the FNSA using upright anteroposterior pelvis radiographs, no significant variability between the two angles was found. Similarly, a study done in India on 110 patients using supine anteroposterior pelvis radiographs concluded that the NSA angle of the contralateral femur can be used as a template during repair [29]. Both studies [28,29] mentioned above agrees with findings of this present study.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, a study done in India on 110 patients using supine anteroposterior pelvis radiographs concluded that the NSA angle of the contralateral femur can be used as a template during repair [29]. Both studies [28,29] mentioned above agrees with findings of this present study.…”
Section: Discussionsupporting
confidence: 90%
“…This is similar to the finding of Chiu et al that amongst the Malaysian population, females had a significantly higher NSA than males [24]. Nevertheless, various studies have shown no differences in NSA between males and females [25,26]. Femoral neck angle measurement has various clinical implications in adults, one potential implication is to aid in determining NSA after an injury.…”
Section: Discussionsupporting
confidence: 87%
“…This is similar to the finding of Chiu et al that amongst the Malaysian population, females had a significantly higher NSA than males [ 24 ]. Nevertheless, various studies have shown no differences in NSA between males and females [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation